The discovery of Jeanne Baret : a story of science, the high seas, and the first woman to circumnavigate the globe - Ridley, Glynis (Crown Publishers, 2010)
In a deeply researched narrative of science, adventure, love, and an unprecedented voyage of discovery, Ridley reveals the true story of Jeanne Baret, the first woman to circumnavigate the globe.